Development of ROV cleaning robot - Mohd Azrul, Mohd Azmi (2022)
Water is essential for life. Humans require clean water on a daily basis to stay healthy. Water is delivered using water storage tanks. The quality of water utilised by users will degrade as sediment builds up in water storage tanks over time. Water utility operators or tank cleaning service providers are required to clean water storage tanks every three years as a result. Remotely operated vehicles (ROYs) are being developed with the goal of creating a low-cost underwater cleaning robot. Another purpose of this project is to evaluate the development system's effectiveness and dependability in operating the system and completing activities like monitoring the underwater state via live-streaming video and cleaning. For solution, the ROY prototype was created with the goal of being as simple, reliable, and cost-effective as possible. The ROY prototype is also built to ensure that its many subsystems work together. For instance, the frame will be built utilising appropriate materials that will be joined to produce a rectangle shape. Other components of the ROY were treated in the same way. Finally, after all of the constructions have been completed, the prototype is tested and updated to verify that it can function securely. Throughout the experiment, it has been discovered that a simple ROY may be built to perform specified duties. The project was deemed a success, but more underwater testing of the prototype is required because many improvements, particularly in the areas of buoyancy and propulsion, can still be made.